Answer:
Step-by-step explanation:
2(3x−5)+4x−10=4x+2(x+6)
Step 1: Simplify both sides of the equation.
2(3x−5)+4x−10=4x+2(x+6)
(2)(3x)+(2)(−5)+4x+−10=4x+(2)(x)+(2)(6)(Distribute)
6x+−10+4x+−10=4x+2x+12
(6x+4x)+(−10+−10)=(4x+2x)+(12)(Combine Like Terms)
10x+−20=6x+12
10x−20=6x+12
Step 2: Subtract 6x from both sides.
10x−20−6x=6x+12−6x
4x−20=12
Step 3: Add 20 to both sides.
4x−20+20=12+20
4x=32
Step 4: Divide both sides by 4.
4x/4 =32/4
x=8
It would be 10 miles since we use Pythagorean Theorem
Answer:
2,1 ig
Step-by-step explanation:
Answer:
2 x 2 x 13
Step-by-step explanation:
2 times 26 = 52
You can break 26 up into 2 times 13.
So, you get 2 times 2 times 13.
Here ya go!!! this should be correct